1985
DOI: 10.1111/j.1550-7408.1985.tb03022.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Potentially Pathogenic Free‐Living Amoebae in Freshwater Lakes1

Abstract: The vertical distribution of thermotolerant (37 degrees C and 45 degrees C) free-living amoebae (FLA) in warm monomictic lakes was determined in relation to the onset of thermal stratification and associated physical and chemical changes. The position of abiotic or biotic particulate layers in the water column was located by using a submersible horizontal beam transmissometer that measures attenuance, or the absorption and scattering of light by particulates in the water column. During mixis, the vertical dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…However, this micro-organism has not been recovered from seawater, suggesting its sensitivity to elevated osmolarity. The vertical distribution of N. fowleri in water has been correlated with the presence of cyanobacteria and eubacteria; therefore, it is possible that the natural function of Naegleria genus is regulating bacterial populations (Kyle & Noblet, 1985). Additionally, the distribution of Naegleria has been associated with the concentrations of manganese and iron in the water column (Kyle & Noblet, 1985;Martinez-Castillo et al, 2015).…”
Section: Ecology and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, this micro-organism has not been recovered from seawater, suggesting its sensitivity to elevated osmolarity. The vertical distribution of N. fowleri in water has been correlated with the presence of cyanobacteria and eubacteria; therefore, it is possible that the natural function of Naegleria genus is regulating bacterial populations (Kyle & Noblet, 1985). Additionally, the distribution of Naegleria has been associated with the concentrations of manganese and iron in the water column (Kyle & Noblet, 1985;Martinez-Castillo et al, 2015).…”
Section: Ecology and Morphologymentioning
confidence: 99%
“…The vertical distribution of N. fowleri in water has been correlated with the presence of cyanobacteria and eubacteria; therefore, it is possible that the natural function of Naegleria genus is regulating bacterial populations (Kyle & Noblet, 1985). Additionally, the distribution of Naegleria has been associated with the concentrations of manganese and iron in the water column (Kyle & Noblet, 1985;Martinez-Castillo et al, 2015). N. fowleri is thermophilic and can survive temperatures of up to 45 C (Kyle & Noblet, 1987).…”
Section: Ecology and Morphologymentioning
confidence: 99%
“…Highest abundances in the water column have been observed at the air/water interface (Davis 1976, Sieburth et al 1976, Davis et al 1978, Kyle & Noblet 1987, on the surfaces of microalgae or macroalgae (Cook et al 1974, Anderson 1977, Kyle & Noblet 1985, Rogerson 1991, or on suspended detrital aggregates (Caron et al 1982, Laybourn-Parry et al 1991, Rogerson & LaybournParry 1992, Arndt 1993. These surfaces presumably provide both substrata for amoeboid locomotion as well as foci for microaggregations of attached bacteria and other prey organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the trophic activities of many of the species are inadequately defined, making it difficult to estimate the contribution of amoebae to energy and elemental flow in natural aquatic communities. Given these limitations, it is not surprising that much of the interest in free-living amoebae has been limited to potential human pathogens (Sawyer et al 1977, 1993, Daggett et al 1982, Kyle & Noblet 1985, Sawyer 1989.…”
Section: Introductionmentioning
confidence: 99%
“…This pond is the result of runoff and contains less organic matter than other sampling sites tested. Kyle and Noblet (1985, 1987 noted that soil was the ideal habitat for free-living amebae and that runoff from rains introduced amebae into water. These investigators reported that significant increases in the numbers of Naegleria and Acanthamoeba were detected in surface water from a shallow water station after a major rainfall.…”
Section: Discussionmentioning
confidence: 98%